Evaluasi Kinerja Sewage Treatment Plant di Bandar Udara International Juanda - Natasya Yulia Rahayu; Restu Hikmah Ayu Murti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Juanda International Airport is an airport located in Sidoarjo, East Java Province and is one of 14 airports managed by PT. Angkasa Pura I. The operational activities of Juanda International Airport produce 1.120 /day wastewater. This study aims to determine the quality of wastewater after the treatment process and evaluate the performance of the STP (Sewage Treatment Plant). Evaluation of STP (Sewage Treatment Plant) performance is based on the existence of one unit that is not operating so that the wastewater produced can potentially not meet the predetermined quality standards. The evaluation is carried out by analyzing wastewater sample at the inlet and outlet, discharge and comparing parameter tes results with predetermined standards. The pramaters used as a reference are BOS, COD, TSS, Ammonia, and Total Coliform. The wastewater outlet produced by Juanda International Airport is in accordance with the Minister of Environment and Forestry Regulation Number 68 of 2016 concerning Domestic Wastewater Quality Standards.